2007
DOI: 10.1007/s00403-007-0781-6
|View full text |Cite
|
Sign up to set email alerts
|

Induction of PDGF-B in TCA-treated epidermal keratinocytes

Abstract: Trichloroacetic acid (TCA) is one of the most widely used peeling agents, and induces full necrosis of the whole epidermis, followed by reconstitution of the epidermis and the matrix of the papillary dermis. The cytotoxic effects of TCA, such as suppressing proliferation of keratinocytes and fibroblasts and protein synthesis by fibroblasts, have already been reported. However, the entire biological mechanism responsible for TCA peeling has yet to be determined. Hypothetical activation effects of TCA treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 12 publications
1
25
0
1
Order By: Relevance
“…TCA, widely used as a peeling agent for the treatment of hyperkeratotic lesions, is known to induce coagulative necrosis of cells and eradication of solar elastosis, which is replaced by a thickened, homogenized band of dermal collagen and formation of normal epidermis . TCA treatment is also followed by the induction of various interleukins and growth factors, contributing to the healing and regeneration processes of the skin . Formic acid, used to remove tattoos and warts, to treat head lice and nits, and as a preservative in cosmetics, causes nonspecific protein cross‐linking and inhibition of mitochondrial function, leading to cell death, fixation and mummification of the tissues …”
Section: Cosmetic Assessment By Investigator and Patientmentioning
confidence: 99%
“…TCA, widely used as a peeling agent for the treatment of hyperkeratotic lesions, is known to induce coagulative necrosis of cells and eradication of solar elastosis, which is replaced by a thickened, homogenized band of dermal collagen and formation of normal epidermis . TCA treatment is also followed by the induction of various interleukins and growth factors, contributing to the healing and regeneration processes of the skin . Formic acid, used to remove tattoos and warts, to treat head lice and nits, and as a preservative in cosmetics, causes nonspecific protein cross‐linking and inhibition of mitochondrial function, leading to cell death, fixation and mummification of the tissues …”
Section: Cosmetic Assessment By Investigator and Patientmentioning
confidence: 99%
“…Previously, we showed that some specific growth factors including platelet-derived growth factor (PDGF)-B are transiently produced by TCA-treated Pam212 murine keratinocytes and human skin specimens after TCA application (25). The sources of PDGF in human dermal wound repair are keratinocytes, as well as platelets and monocytes.…”
Section: Three Pathways In Tca Peelingmentioning
confidence: 99%
“…Culture of murine epidermal cell clone (Pam212) in the presence of TCA was described previously. 1 In brief, Pam212 was cultured in Dulbecco's modified Eagles medium (DMEM) supplemented with 5% fetal bovine serum and appropriate amounts of antibiotics and antimycotics (penicillin, streptomycin and amphotericin B) (Life Technologies, Carlsbad, CA, USA). The stock solution of TCA was prepared as a concentration of 5% (w ⁄ v) in DMEM and added at indicated concentrations to the cell culture showing approximately 70% confluency.…”
Section: Cell Culturementioning
confidence: 99%
“…This fundamentally toxic reagent induces full necrosis of the whole epidermis, and the following reconstitution of the epidermis and the papillary dermis might have an important role in its rejuvenating effects. Previously, we have shown that some specific growth factors including platelet‐derived growth factor (PDGF)‐B, as well as various inflammatory cytokines, are transiently produced by TCA‐treated keratinocytes before their necrosis 1 . Induction of these growth factors and cytokines would be beneficial to better and faster wound healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation